Acute and Subacute Toxicity Study of Essential Oil of Cymbopogon Martini in Mice - Kassahun Dires Ayenew; Yihenew Sewale; Yosef Eshetie Amare; Amare Ayalew (Journal of Toxicology)
Background. Local Ethiopians regularly use Cymbopogon martini for cosmetic purposes. The plant’s safety, however, is not supported by any solid facts. This investigation aimed to evaluate the acute and subacute toxicities of C. martini essential oil in mice. Methods. The essential oil was analyzed using GC-MS. The approach outlined by Chinedu et al., 2013 has been used to calculate the median lethal dose. According to organization for economic cooperation and development (OECD) 407 standard, a 28-day repeated dose oral toxicity study was carried out on female mice. Three groups of ten experimental mice each were distributed at random. Group I received the same saline volume and was considered the control. Groups II and III were treated with doses of C. martini of 500 mg/kg and 1000 mg/kg, respectively, of body weight. Hematological and biochemical markers were assessed. The liver and kidney were taken out after the sacrifice using sodium pentobarbital for pathological analysis. Results. Geraniol (40.89%) was the predominant component in the essential oil composition of C. martini with cyclofenchene (13.91%), myrcene (9.34%), 2, 4, 6, octatriene, 2, 6, dimethyl (8.20%), and ocimene (5.93%) being present in small amounts. The LD50 of C. martini essential oil was discovered to be greater than 5000 mg/kg body weight. During a 4-week follow-up period, mice treated with C. martini, the essential oil, at doses of 500 mg/kg or 1000 mg/kg body weight showed no evidence of toxicity or mortality. Biochemical and hematological parameters were not significantly altered in mice treated with the essential oil of C. martini compared with the control group. Histopathological evaluation of the liver and kidney did not exhibit any adverse results. Conclusions. The essential oil of C. martini from Ethiopia is considered relatively safe and nontoxic.